2010
DOI: 10.2478/10004-1254-61-2010-1990
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of HCV Infection Among Nursing Students of the Medical College of Bitola

Abstract: Healthcare workers are at risk of occupationally-acquired viral infections such as human immunodefi ciency virus (HIV), hepatitis B (HBV), and hepatitis C (HCV). HCV is parenterally transmitted and has been found in every part of the world. This cross-sectional study was conducted to establish the awareness and attitude about HCV infections among 210 full-time and part-time nursing students of the Medical College in Bitola, Macedonia 'from May to June 2009. For this purpose we used a self-administered question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Regarding the mode of HCV transmission, our study has shown that the level of awareness among all the participants was very good. These findings are similar to findings reported by the study in the University of LOME students [11] and also in medical college. Bitola [10] and University of Dammam have also shown high level of awareness of HCV transmission [12].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the mode of HCV transmission, our study has shown that the level of awareness among all the participants was very good. These findings are similar to findings reported by the study in the University of LOME students [11] and also in medical college. Bitola [10] and University of Dammam have also shown high level of awareness of HCV transmission [12].…”
Section: Discussionsupporting
confidence: 92%
“…These results were similar to findings reported by the study in University of Lome students. [14] In the Medical College of Bitola, students showed a high-level of awareness of HCV transmission,[13] and more than half of the medical students in medical colleges of Karachi, Pakistan, revealed excellent knowledge of HBV and HCV transmission. [12]…”
Section: Discussionmentioning
confidence: 99%
“…[11] However, the studies from medical colleges of Karachi[12] and Bitola in Macedonia[13] showed medical students' knowledge of HCV as satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…A study among Turkish nursing students found high levels of negative attitude and fear of contagion of HIV as a reason for being unwilling to care for HIV-infected patients [5]. A study among nursing students in Macedonia found that although most students had high level of HIV knowledge, a majority avoided people living with HIV (PLHIV) [6]. Another study among nursing students in Greece found that more than a third of the nursing students believe that mosquitoes can transmit HIV virus [7].…”
Section: Introductionmentioning
confidence: 99%